Analisis Kebutuhan Pendidik dan Tenaga Kependidikan di Sanggar Kegiatan Belajar Kota Makassar - M. Ali Latif; Muhammad Asri; Nasrah Natsir (Seminar Nasional LP2M UNM, 2022)
ABSTRACT. This study aims to determine: (1) the needs of educators and education personnel in Makassar City SKB (2) the skills/expertise of educators and education personnel needed, and (3) the constraints of the SKB in implementing non-formal education programs. The research includes descriptive research. Research subjects SKB Ujungpandang and Biringkanaya. The data collection instrument used interview, observation and documentation guidelines. Based on the data analysis, it was concluded that (1) the need for educators (Pamong Learn) at the Makassar City SKB was 21 people, who had the skills/competence to design learning/training programs, and teach subjects in the Package B and Package C equivalency education programs. (2 ) The need for education staff at the Makassar City SKB is 9 people, who have skills/expertise in the field of administration and computers. (3) Obstacles experienced by the SKB in implementing the program: (a) lack of teaching staff (Pamong Belajar), especially those who teach English and Mathematics subjects (b) lack of ability of educational staff (administrative staff) in preparing program planning, and (c) the minimum operational budget for the implementation of learning and/or training programs.  Keywords: Needs, Educators, Education Personnel. SKB